2016
DOI: 10.4103/0970-9185.175649
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative analgesia for cleft lip and palate repair in children

Abstract: Acute pain such as postoperative pain during infancy was ignored approximately three decades ago due to biases and misconceptions regarding the maturity of the infant's developing nervous system, their inability to verbally report pain, and their perceived inability to remember pain. More recently, these misconceptions are rarely acknowledged due to enhanced understanding of the developmental neurobiology of infant pain pathways and supraspinal processing. Cleft lip and palate is one of the most common congeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…Orofacial clefts, such as cleft palate, are a common congenital abnormality associated with severe postoperative pain. 190 , 191 One study evaluated the efficacy of bilateral suprazygomatic maxillary nerve blocks on postoperative analgesia outcomes in pediatric patients undergoing cleft palate repair. 61 The authors reported that bilateral suprazygomatic maxillary nerve blocks with ropivacaine lowered the overall morphine consumption compared with placebo after 48 hours following surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Orofacial clefts, such as cleft palate, are a common congenital abnormality associated with severe postoperative pain. 190 , 191 One study evaluated the efficacy of bilateral suprazygomatic maxillary nerve blocks on postoperative analgesia outcomes in pediatric patients undergoing cleft palate repair. 61 The authors reported that bilateral suprazygomatic maxillary nerve blocks with ropivacaine lowered the overall morphine consumption compared with placebo after 48 hours following surgery.…”
Section: Resultsmentioning
confidence: 99%
“…There is a growing awareness in recent years of the need for children's complete wellbeing in postoperative periods, and not only being pain free. Sedation and other adverse events related to opioids do not help in achieving this goal [19]. Postoperative pain may extend beyond the nerve block resolution duration.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical infiltration and various nerve blocks are used to repress the hemodynamic effects and to achieve adequate postoperative pain relief [ 5 6 16 ]. However, there is no single effective block for CP surgeries and a multimodal approach for to pain management has been recommended [ 17 ]. Despite the lack of FDA labeling for pediatric use, dexmedetomidine has been increasingly used in these patients over recent years [ 7 8 18 ].…”
Section: Discussionmentioning
confidence: 99%